Saved by Faith Not Your Body: Towards The Theology of Disability - Sitanggang, Pintor Marihot (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2024)
This article describes that the perfection of God’s creation was guaranteed by faith, must be hold and lived in the life of the believers. Physical weakness (difable) is not a condition cause decreasing the perfection of God’s creation. Difable is not decreasing or weakening the existence and essence of human being as the body of Christ which was loved and saved by the blood of Christ. This article used the library research in theology, explored the love of God in the life of human being. The result showed that the church must develop the ministries of educating and empowering disable people (people with the special need). They are perfect as the body of Christ because the God itself is perfect. God is perfect so the creation is perfect too. Human being was perfected by the love of God.